2011
DOI: 10.1007/s00417-011-1724-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time polymerase chain reaction and intraocular antibody production for the diagnosis of viral versus toxoplasmic infectious posterior uveitis

Abstract: For the diagnosis of viral or toxoplasmosis-associated intraocular inflammation, the usefulness of laboratory diagnosis tools (RT-PCR and GWC) depends on parameters other than the sensitivity of the tests. Certain patient characteristics such as the age of the patients, immune status, duration since the onset of symptoms, retinitis area, predominant site and extent of inflammation within the eye should orientate the rational for the choice of laboratory testing in analysis of intraocular fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
(53 reference statements)
0
30
1
Order By: Relevance
“…Errera et al recently reported the sensitivity and specificity of real-time PCR and GWC in intraocular samples of posterior uveitis patients' collected at different time points during the clinical course. GWC showed higher diagnostic values for T. gondii detection, especially when the test was carried out late in the disease course [37]. However, in our study, GWC for T. gondii was found positive in one patient only.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Errera et al recently reported the sensitivity and specificity of real-time PCR and GWC in intraocular samples of posterior uveitis patients' collected at different time points during the clinical course. GWC showed higher diagnostic values for T. gondii detection, especially when the test was carried out late in the disease course [37]. However, in our study, GWC for T. gondii was found positive in one patient only.…”
Section: Discussioncontrasting
confidence: 77%
“…In our study the aqueous humor and the vitreous humor samples had similar diagnostic values. It is reported that the diagnostic efficacy of aqueous humor analysis can be improved with the concurrent use of GWC and PCR [7,37]. Errera et al recently reported the sensitivity and specificity of real-time PCR and GWC in intraocular samples of posterior uveitis patients' collected at different time points during the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of ocular toxoplasmosis was always confirmed by intraocular fluid assessment. [8][9][10][11] Diagnosis of presumed ocular toxoplasmosis was based on typical clinical features of unilateral focal necrotizing retinitis sometimes associated with typical old pigmented scars. All other specific diagnoses were performed according to current diagnostic criteria.…”
Section: Assessment Of Determinants and Outcomesmentioning
confidence: 99%
“…It's very important to remember that PCR is strongly positive in the first days after ocular lesion clinical manifestations, whereas immunoblotting sensitivity that is low at the beginning increases along time, so time interval between ocular manifestations beginning and humour aqueous analysis influence strongly intraocular antibody synthesis detection (4).…”
Section: Discussionmentioning
confidence: 99%